Features of Diurnal Rhythm of Blood Pressure at Chronic Pyelonephritis in Children - L.I. Vakulenko; V.I. Kondratiyev; A.V. Vakulenko (Zaslavsky O.Yu., 2012)
In the article there are given the results of ambulatory blood pressure monitoring in 40 children with chronic pyelonephritis. In 30 % of cases there was revealed arterial hypertension, which was 3 times more frequent in boys. The course of chronic pyelonephritis is more often associated with nocturnal hypertension. The features of diurnal rhythm of blood pressure at chronic pyelonephritis in children are characterized with frequent combination of labile hypertension and higher level of nocturnal diastolic blood pressure.